2007
DOI: 10.1111/j.1440-1754.2007.01202.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal circumcision: Effects on breastfeeding and outcomes associated with breastfeeding

Abstract: There was no evidence of an association between neonatal circumcision status and breastfeeding outcomes, or between circumcision status and health and cognitive ability outcomes associated with breastfeeding, and the findings do not support the view that neonatal circumcision disrupts breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 29 publications
2
33
0
1
Order By: Relevance
“…In contrast, in a longitudinal study of New Zealand boys circumcised in 1977, MC had no adverse effect on breastfeeding outcomes or cognitive ability later in childhood 26 . In another follow-up study, of Swedish boys after MC, the boys showed no adverse psychological effect of MC 112 …”
Section: Procedural and Post-operative Pain In Infantsmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, in a longitudinal study of New Zealand boys circumcised in 1977, MC had no adverse effect on breastfeeding outcomes or cognitive ability later in childhood 26 . In another follow-up study, of Swedish boys after MC, the boys showed no adverse psychological effect of MC 112 …”
Section: Procedural and Post-operative Pain In Infantsmentioning
confidence: 90%
“…The risk of major surgical mishaps with MC, however, is extremely low and the benefits gained from MC far exceed risks 2 , 5 , 8 , 9 . Furthermore, there is no long-term adverse effect of infant MC on psychological 26 , 27 or sexual 28 – 33 outcomes. Systematic reviews have found no adverse effect of MC on sexual function, 28 , 29 , 33 sensitivity, or satisfaction 29 .…”
Section: Benefits Versus Risksmentioning
confidence: 99%
“…As expected, risk of asthma was independent of the boys' foreskin status, which is in accordance with prior findings for asthma in the first years of life. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Circumcision status was not associated with health in infancy, cognitive ability outcomes in later childhood or breastfeeding. 9 On the other hand, reports usually include subjective descriptions by adult observers based on the visual appraisal of neonatal suffering. 10 Quantitative reports indicate higher intravenous cortisol levels in neonates ~30 min following circumcision conducted 57–80 h after birth.…”
Section: Introductionmentioning
confidence: 99%